Numerical study of cold-start performances of a medium compression ratio direct-injection twin-spark plug synchronous ignition engine fueled with methanol. (1st February 2021) - Gong, Changming; Sun, Jingzhen; Chen, Yulin; Liu, Fenghua
Highlights: Model of twin-spark plug synchronous ignition engine fueled with methanol was built. Cold start Performances were studied for simulation evaluation. Methanol late-injection strategy of medium compression ratio engine was used. The emissions of twin-spark plug are better than that of single-spark plug. Preferred combustion control parameters can obtain the best performance compromise. Abstract: The cold-start mixture preparation, combustion and emissions behaviors of a medium compression ratio direct-injection twin-spark plug synchronous ignition engine fueled with methanol were numerically simulated. Simulation results display that the methanol injection timing, ignition timing and the global equivalence ratio had an important influence on the concentration distribution of methanol-air mixture, the flow velocity, and the density of the flame surface during cold start. Ignition delay period reached the shortest at injection timing 70°CA BTDC. Ignition delay period for injection timing 130°CA BTDC and 50°CA BTDC increased 209% and 45.5% compared to injection timing 70°CA BTDC, respectively. Ignition delay period reached the shortest at ignition timing 21°CA BTDC. Ignition delay period of twin-spark plug was shorter than that of single-spark plug at the same equivalence ratio. There existed the maximum in-cylinder pressure, maximum heat release rate, maximum in-cylinder temperature, lowest unburned methanol and soot emissions, and highest NOX emissions at injection timing 70°CA BTDC. The maximum in-cylinder pressure, maximum heat release rate, and maximum in-cylinder temperature gradually increased with the advance of ignition timing. Injection timing 70°CA BTDC, ignition timing 21°CA BTDC, and equivalence ratio 0.9 could obtain the best cold start performance compromise using twin-spark plug ignition mode. At equivalence ratio 1.0, twin-spark plug ignition had better combustion performances, lower unburned methanol and soot emissions, and higher NOX emissions compared with single-spark plug ignition. Twin-spark plug synchronous ignition had more advantageous to cold starting ignition compared with single-spark plug ignition for a medium compression ratio direct-injection spark-ignition methanol engine.